2017
DOI: 10.1177/0018726717726861
|View full text |Cite
|
Sign up to set email alerts
|

When does an issue trigger change in a field? A comparative approach to issue frames, field structures and types of field change

Abstract: Citation: Furnari, S. (2018). When does an issue trigger change in a field? A comparative approach to issue frames, field structures and types of field change. This is the accepted version of the paper.This version of the publication may differ from the final published version.Permanent repository link: http://openaccess.city.ac.uk/19485/ Link to published version: http://dx. AbstractPrevious research has shown that institutional fields evolve around issues, but has devoted less attention to explain why certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 97 publications
(219 reference statements)
2
44
0
1
Order By: Relevance
“…It would also seem worthwhile to extend such research to encompass theoretical comparisons across institutional fields. Comparative research across institutional fields is still scarce (Micelotta et al 2017, Furnari, 2018 and has only started to feature in the PMM literature (Chiwamit et al 2014, Rautiainen et al 2017. However, such research has considerable potential to further systematic theory development regarding how meanings that evolve in institutional fields (Purdy et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It would also seem worthwhile to extend such research to encompass theoretical comparisons across institutional fields. Comparative research across institutional fields is still scarce (Micelotta et al 2017, Furnari, 2018 and has only started to feature in the PMM literature (Chiwamit et al 2014, Rautiainen et al 2017. However, such research has considerable potential to further systematic theory development regarding how meanings that evolve in institutional fields (Purdy et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In advancing a multi-level perspective, that is attentive to the socio-political dimensions of framing, I follow an emerging stream of institutional research , Chreim 2006, Ansari et al 2013, Meyer and Höllerer 2010, Jonsson and Lounsbury 2017, Furnari 2018) building on the social movement literature and, especially, Snow et al's (1986) seminal work on frame alignment. By frame alignment Snow et al (1986) referred to the extent to which the frames mobilised by particular actors are congruent with the frames enacted by and guiding the actions of other actors in specific social contexts.…”
Section: The Concept Of Framing In Institutional Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…When McAdam and Scott (2005) initially discussed the notion of field settlement, they suggested that there is likely to be a range of possible settlements whereby small settlements may ultimately culminate in profound institutional changes. Indeed, recent work examining field settlements has argued that they often serve as an indicator for further substantive action (Furnari, 2018;Litrico & David, 2017;Zietsma, Groenewegen, Logue, & Hinings, 2017). Yet, the settlement around responsible investment that we observed in this case appeared to reinforce the status quo rather that spur substantive action.…”
Section: Ambiguous Frames and Field Settlementsmentioning
confidence: 99%